Hubungan Pengetahuan Ibu Tentang Gizi Dan Pendapatan Orang Tua Terhadap Peilaku Konsumsi Buah Dan Sayur Pada Balita 6 Bulan - 5 Tahun Di Wilayah Kerja Puskesmas Peusangan Selatan Kabupaten Bireuen - Nafis, Maghfiratun; Safitri, Dessy Widya; Pelupessy, Grace Yosephine; Tanjung, Putri Habibah; Marbun, Rasyida Afifah; Wilda, Zahratul; Haryana, Nila Reswari (Peneliti.net, 2025)
Indonesia is a country with a low level of fruit and vegetable consumption. Based on Riskesdas 2018, 95.5% of toddlers do not consume fruits and vegetables. Based on WHO, the level of fruit and vegetable consumption of toddlers is still relatively low, namely 95%. Lack of fruit and vegetable intake will result in a risk of death from digestive tract cancer of 14%, a risk of death from coronary heart disease of 11%, and death from stroke of 9%. Based on this background, researchers are interested in conducting research on